MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI LUAS BANGUN RUANG MELALUI PENGGUNAAN MEDIA BANGUN RUANG PADA SISWA KELAS VI SDN BANYUAJUH 5 - vikram moh vikram dwi putra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Bakti Indonesia, 2023)
Education is a conscious and planned effort to create an environment and learning process that enables students to actively realize their potential. Education is organized to obtain religious spiritual strength, self-control, personality, intelligence, noble character and skills needed in society, nation and state. Various steps to improve the curriculum, improve the teaching system, improve the quality of teacher qualifications, etc. are investments to improve the quality of learning. Some of the causes of low student learning outcomes on geometric surfaces are abstract materials on geometric surfaces. Students have difficulty distinguishing the sides of a flat shape from a geometric shape, the broad concept of an unstable flat shape, and the use of inappropriate materials or not using media that can improve student learning outcomes. Another problem is teachers. When teaching in class, the majority of teachers still pay little attention to students' thinking skills, the media used is less flexible, meaning that it is difficult to increase student motivation and learning models are usually eliminated. Coupled with the use of a learning approach that makes students passive in the teaching and learning process, resulting in students not being interested in the lesson. This study aims to achieve the goal of increasing student learning outcomes through the use of geometric media in learning mathematics. This type of research is classroom action research. According to Wardan (2002: 1.4) Educational action research is research conducted by teachers in their classes and in collaboration between researchers and practitioners (teachers and school principals). The research process was carried out in two cycles (cycles I and II), each of which included problem identification, planning, action and observation, and reflection. The results of the first cycle test showed that out of 25 students in class VI only 14 students or (56%) were declared to have completed their studies by obtaining a score above the KKM (65), while 11 students or (44%) were stated to have not completed their studies with scores below 65 with an average value of 65.7. The results of the ability test in cycle II showed that 25 students in class VI could be declared complete in learning, but there were several students who got the same results as the KKM. From the analysis of test results in cycle II, it was found that the class average reached 82.9 out of 25 students, all students had scored 65 and above or 100%. Keywords: learning mathematics, learning media, learning outcomes